Comparative Peptidomics Analysis of Fermented Milk by Lactobacillus delbrueckii ssp. bulgaricus and Lactobacillus delbrueckii ssp. lactis - Hongji Ye; Xinyi Zhang; Yang Jiang; Min Guo; Xiaoming Liu; Jianxin Zhao; Hao Zhang; Wei Chen (Foods, 2021)
Few studies have investigated the peptidomics of fermented milk by Lactobacillus delbrueckii. The aim of the present study was to interpret the peptidomic pattern of the fermented milk by five strains of L. delbrueckii ssp. bulgaricus and ssp. lactis prior to and after the simulated gastrointestinal digestion in vitro. The results indicated variations in the peptidomics among the samples, particularly between the samples of different subspecies. The peptides originating from β-casein were abundant in the samples of ssp. bulgaricus, whereas the peptides derived from αs1-casein and αs2-casein were more likely to dominate in those of ssp. lactis. For β-casein, the strains of ssp. bulgaricus displayed extensive hydrolysis in the regions of (73–97), (100–120), and (130–209), whereas ssp. lactis mainly focused on (160–209). The digestion appears to reduce the variations of the peptidomics profile in general. Among the five strains, L. delbrueckii ssp. bulgaricus DQHXNS8L6 was the most efficient in the generation of bioactive peptides prior to and after digestion. This research provided an approach for evaluating the peptide profile of the strains during fermentation and digestion.